Telomeric repeat-containing RNA TERRA: a noncoding RNA connecting telomere biology to genome integrity - Cusanelli, Emilio; Chartrand, Pascal (Frontiers in Genetics, 2015)
Telomeres are dynamic nucleoprotein structures that protect the ends of chromosomes from degradation and activation of DNA damage response. For this reason, telomeres are essential to genome integrity. Chromosome ends are enriched in heterochromatic marks and proper organization of telomeric chromatin is important to telomere stability. Despite their heterochromatic state, telomeres are transcribed giving rise to long noncoding RNAs (lncRNA) called TERRA (telomeric repeat-containing RNA). TERRA molecules play critical roles in telomere biology, including regulation of telomerase activity and heterochromatin formation at chromosome ends. Emerging evidence indicate that TERRA transcripts form DNA-RNA hybrids at chromosome ends which can promote homologous recombination among telomeres, delaying cellular senescence and sustaining genome instability. Intriguingly, TERRA RNA-telomeric DNA hybrids are involved in telomere length homeostasis of telomerase-negative cancer cells. Furthermore, TERRA transcripts play a role in the DNA damage response triggered by dysfunctional telomeres. We discuss here recent developments on TERRA’s role in telomere biology and genome integrity, and its implication in cancer.